2011
DOI: 10.1002/mc.21857
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functional variant in SPLUNC1 associated with nasopharyngeal carcinoma susceptibility among Malaysian Chinese

Abstract: Nasopharyngeal carcinoma (NPC) is a multifactorial and polygenic disease with high incidence in Asian countries. Epstein-Barr virus infection, environmental and genetic factors are believed to be involved in the tumorigenesis of NPC. The association of single nucleotide polymorphisms (SNPs) in LPLUNC1 and SPLUNC1 genes with NPC was investigated by performing a two-stage case control association study in a Malaysian Chinese population. The initial screening consisted of 81 NPC patients and 147 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…After eliminating polymorphic loci represented in less than two articles, 15 SNPs were found to be significantly associated with the risk of NPC: TP53 (rs1042522, C>G) [ 14 18 ], GSTM1 (+/DEL) [ 19 – 21 ], IL-10 (rs1800896, A>G) [ 22 , 23 ], GABBR1 (rs2076483, T>C; rs29232, G>A) [ 24 , 25 ], MDM2 (rs2279744, T>G) [ 16 , 26 ], miR-146a (rs2910164, C>G) [ 27 , 28 ], MDS1-EVI1 (rs6774494, G>A) [ 29 , 30 ], XPC (rs2228000, C>T) [ 30 , 31 ],, HCG9 (rs3869062, A>G; rs16896923, T>C) [ 24 , 25 ], HLA-F (rs3129055, T>C) [ 24 , 25 ], MMP2 (rs243865, C>T) [ 32 , 33 ], SPLUNC1 (rs2752903, T>C; rs750064, A>G) [ 34 , 35 ]. Among these, two SNPs (in the TP53 and GSTM1 genes) were addressed in more than two relevant articles, while each of the others were mentioned in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After eliminating polymorphic loci represented in less than two articles, 15 SNPs were found to be significantly associated with the risk of NPC: TP53 (rs1042522, C>G) [ 14 18 ], GSTM1 (+/DEL) [ 19 – 21 ], IL-10 (rs1800896, A>G) [ 22 , 23 ], GABBR1 (rs2076483, T>C; rs29232, G>A) [ 24 , 25 ], MDM2 (rs2279744, T>G) [ 16 , 26 ], miR-146a (rs2910164, C>G) [ 27 , 28 ], MDS1-EVI1 (rs6774494, G>A) [ 29 , 30 ], XPC (rs2228000, C>T) [ 30 , 31 ],, HCG9 (rs3869062, A>G; rs16896923, T>C) [ 24 , 25 ], HLA-F (rs3129055, T>C) [ 24 , 25 ], MMP2 (rs243865, C>T) [ 32 , 33 ], SPLUNC1 (rs2752903, T>C; rs750064, A>G) [ 34 , 35 ]. Among these, two SNPs (in the TP53 and GSTM1 genes) were addressed in more than two relevant articles, while each of the others were mentioned in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…This gene family is expressed mostly on the epithelial surface of the respiratory and digestive tracts and play a role in signal transduction of external stimuli. SPLUNC1 is a natural immune protective molecule; it has anti-inflammatory actions, tumor suppressor effects, and helps maintain the normal physiology of the upper respiratory tract [ 34 , 35 ]. Our analysis indicates that miR-146a (rs2910164, C>G), HCG9 (rs3869062, A>G), HCG9 (rs16896923, T>C), MMP2 (rs243865, C>T), GABBR1 (rs2076483, T>C), and TP53 (rs1042522, C>G) are associated with decreased susceptibility to NPC, while the other SNPs might contribute instead to increased risk of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-associated single nucleotide polymorphisms (SNPs) are enriched in regulatory regions (Ernst et al, 2011; Hindorff et al, 2009; Maurano et al, 2012). Many recent studies have identified links between disease-associated variants in regulatory DNA and a broad spectrum of human diseases, including cancer (Demichelis et al, 2012; Huang et al, 2013; Horn et al, 2013; Jiang et al, 2011; Liu et al, 2011; Lubbe et al, 2012; Schodel et al, 2012; Yew et al, 2012), congenital heart disease (Zhao et al, 2012), inflammatory lung disease (Han et al, 2012), multiple sclerosis (Alcina et al, 2012), Alzheimer’s disease (Gaj et al, 2012), abdominal aortic aneurysm (Bown et al, 2011), amyotrophic lateral sclerosis (Iida et al, 2011) and coronary artery disease (Harismendy et al, 2011). Disease-associated genetic variants in regulatory regions are most often found in regions that are utilized in a cell type-specific manner and are associated with diseases of the corresponding cell type (Ernst et al, 2011; Maurano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the link between disease-associated variants in regulatory DNA and breast cancer (Jiang et al, 2011), prostate cancer (Demichelis et al, 2012), colorectal cancer (Lubbe et al, 2012), renal cancer (Schodel et al, 2012), lung cancer (Liu et al, 2011), nasopharyngeal cancer (Yew et al, 2012) and melanoma (Huang et al, 2013; Horn et al, 2013). The genome instability that is a hallmark of cancer almost certainly contributes to further alter sequences in regulatory regions that can promote tumor progression.…”
Section: Misregulated Gene Expression In Diseasementioning
confidence: 99%
“…Lifestyle trends such as smoking, alcohol intake, consumption of salted fish or preserved food and occupational hazard all contribute to increased risk of NPC . Many candidate genes have been suggested in NPC susceptibility, in particular the major histocompatibility complex (MHC) region, with great focus on the antigen presenting molecule HLA‐A gene . The association of the HLA‐A with NPC susceptibility has been well‐documented in linkage studies, candidate gene approaches and GWAS studies .…”
mentioning
confidence: 99%